Neurotrauma Research in Latin America - Andrés Rubiano; Angela Rios (Revista de Pesquisa : Cuidado é Fundamental Online, 2014)
Recently, the global burden of disease study, presented by the world health organization, call the attention of the research community, showing that trauma still remains as a major public health problem in Central and South America.1